Polycaprolactone‐chitosan‐polypyrrole conductive biocomposite nanofibrous scaffold for biomedical applications. Issue 2 (25th October 2019) - Talebi, Alireza; Labbaf, Sheyda; Karimzadeh, Fathallah
Abstract: In this study, polycaprolactone/chitosan/polypyrrole (PCL/chitosan/PPy) conductive composite nanofibrous scaffold is fabricated. For this purpose, initially, a polymer blend of PCL/chitosan (7:3) and (4:1) was selected and then 1, 2.5, 5 and 7.5 wt% of PPy was added to each solution. A range of techniques were applied to study the chemical, physical and biodegradability properties of the resultant fibrous mats. According to scanning electron microscope (SEM) images, with the addition of PPy to the PCL/chitosan blend, the size of the fiber diameter decrease. There was significant increase in the electrical conductivity of the mats such that the electrical conductivity of PCL/chitosan was around 0.1 S/cm but increased to 2 S/cm in biological environment with the addition of 7.5% PPy. Hydrophobicity was found to improve with the addition of PPy as water contact angle changed from 120 ± 10° for PCL/chitosan to 133 ± 18° at 7.5% PPy. The incorporation of PPy within the PCL/chitosan matrix was found to positively influence the overall properties of nanofibrous structure, making them suitable for biomedical applications.